Análise Estatística da Concentração de Potássio Obtida por Aerolevantamentos Geofísicos em Diferentes Formações Geológicas na Região de Santa Maria (RS) - PEREIRA, JOÃO EDUARDO DA SILVA; DA SILVA, JOSÉ LUIZ SILVÉRIO; STRIEDER, ADELIR JOSÉ; PIRES, CARLOS ALBERTO DA FONSECA (Pesquisas em Geociências, 2007)
<!-- .p { text-align: justify; } --> The present work was developed in outcrops of Santa Maria region, southern Brazil, Rio Grande do Sul State. Statistic evaluations were applied in different rock types. The possibility to distinguish different geologic units, sedimentary and volcanic (acid and basic types) by means of the statistic analyses from the use of airborne gamma-ray spectrometry integrating potash radiation emissions data with geological and geochemistry data is discussed. This Project was carried out at 1973 by Geological Survey of Brazil/Companhia de Pesquisas de Recursos Minerais. The Camaquã Project evaluated the behavior of potash concentrations generating XYZ Geosof 1997 format, one grid, thematic map and digital thematic map files from this total area. Using these data base, the integration of statistics analyses in sedimentary formations which belong to the Depressão Central do Rio Grande do Sul and/or to volcanic rocks from Planalto da Serra Geral at the border of Paraná Basin was tested. Univariate statistics model was used: the media, the standard media error, and the trust limits were estimated. The Tukey’s Test was used in order to compare mean values. The results allowed to create criteria to distinguish geological formations based on their potash content. The back-calibration technique was employed to transform K radiation to percentage. Inside this context it was possible to define characteristic values from radioactive potash emissions and their trust ranges in relation to geologic formations. The potash variable when evaluated in relation to geographic Universal Transverse Mercator coordinates system showed a spatial relation following one polynomial model of second order, with one determination coefficient. The statística 7.1 software Generalist Linear Models produced by Statistics Department of Federal University of Santa Maria/Brazil was used.